PENGARUH MODEL PEMBELAJARAN GENERATIF TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI PEMANASAN GLOBAL - Fela Elwitriana; Suhendar Suhendar; Aa Juhanda (Universitas Negeri Medan, 2019)
This study aims to find how students' critical thinking skills after learning to use generative learning models in science learning material on global warming. This type of research is a quasi-experimental study with a population of 2 classes taken from class VII SMP in one of the cities of Sukabumi. The research sample was selected using a purposive sampling technique. The research design used in this study was the Nonequivalent Control Group Design. The instrument used in this study is a multiple-choice test of 15 items, each of which has been declared valid and reliable. Based on the data requirements test, it is known that the results of the research data are normally distributed and the two classes have the same variance (homogeneous). From the data analysis, it is known that the average value of the posttest of the experimental class students with the generative learning model is 84.50 and the average value of the posttest of the control class students without using the generative learning model is 62.19. There is a significant difference in student learning outcomes, this is evidenced by the Z-test obtained by Zcount> Ztable (3.72 > 1.96) so this study rejects H0 and accepts H1. Thus, it can be concluded that there are effects of learning outcomes on the critical thinking skills of students who take part in learning by using generative learning models on global warming material.